Leucine Supplementation Improves Effort Tolerance of Rats With Hyperthyroidism - Fidale, Thiago Montes; Antunes, Hanna Karen Moreira; Roever, Leonardo; Gonçalves, Alexandre; Puga, Guilherme Morais; Silva, Romeu Paulo Martins; de Resende, Fernando Nazário; de Souza, Fernanda Rodrigues; Fidale, Beatriz Montes; Lizardo, Frederico Balbino; Resende, Elmiro Santos (Frontiers in Physiology, 2018)
Leucine is a regulator of protein metabolism in vivo and information on its action on effort tolerance of both animals and humans with hyperthyroidism is scarce. The objective of the present study was to verify the influence of leucine supplementation on the effort tolerance of Wistar rats with experimental hyperthyroidism. 40 animals were divided into four groups of ten: control (C), hormone (H), leucine (L), and hormone + leucine (HL). Hyperthyroidism was induced by daily administration of 20μg•100 g-1 of levothyroxine sodium in aqueous suspension by gavage. Leucine was supplemented by adding 5% of the amino acid to the conventional feed. The animals' blood was collected by cardiac puncture to analyze TSH, T4, and T3 levels. The effort tolerance was determined by the swimming test with a 7% load attached to animals’ tails. Statistical analysis was performed using the Shapiro-Wilk normality test, followed by the analysis of variance (ANOVA) of repeated measures of two factors (treatment x time) and Tukey post-hoc, with a significance level of p <0.05. Administering thyroid hormone increased the swimming performance of rats after 14 and 21 days, but with a drop in performance at 28 days. The HL group, on the other hand, had a significantly higher swimming performance compared to the other groups after 28 days of treatment. Leucine supplementation associated with the experimental model of hyperthyroidism improved the performance of rats in a swimming test after 28 days of treatment.